Akkermansia muciniphila: new insights into resistance to gastrointestinal stress, adhesion, and protein interaction with human mucins through optimised in vitro trials and bioinformatics tools - Vergalito, Franca; Bagnoli, Diletta; Maiuro, Lucia; Pannella, Gianfranco; Palombo, Valentino; Testa, Bruno; Coppola, Francesca; Di Marco, Roberto M. A.; Tremonte, Patrizio; Lombardi, Silvia J.; Iorizzo, Massimo; Coppola, Raffaele; et al. (Frontiers in Microbiology, 2024)
According to the FAO/WHO guidelines, selection of probiotics requires the assessment of survival under gastrointestinal stress and adhesion to human epithelial cells. These attributes were evaluated on Akkermansia muciniphila ATCC BAA-835 simulating the gastrointestinal transit (GIT) immediately followed by adhesion to human intestinal cell lines (CaCo2, HT-29, and HT-29-MTX) as an alternative approach to in vitro methods performed with fresh cells in each trial. The survival rate after GIT, as determined by plate counts and fluorescent probes, was significantly higher for A. muciniphila (about 8 Log CFU/mL) than for the probiotic Lacticaseibacillus rhamnosus GG ATCC 53103 (about 3 Log CFU/mL). The use of Live/Dead assay highlighted that A. muciniphila forms cell aggregates in the gastric phase as protective mechanism, explaining its high viability in the intestine. The rate of adhesion to human cell lines was always lower for strains tested after simulated GIT than for strains that did not undergo simulated GIT. Akkermansia muciniphila exhibited significantly higher adhesion than Lbs. rhamnosus GG, particularly to the mucus-secreting HT-29-MTX cells across a range of concentrations (2–8 Log CFU/mL). Finally, the bioinformatic analysis of A. muciniphila proteome confirmed the Amuc_1434 as a potential factor in binding to the human MUC2 protein.